Assessment of Phytochemical Properties of Nigella sativa Seeds Essential Oil and Its Potential Antimicrobial Activity against Staphylococcus aureus in the Context of Safety Profiles and Therapeutic Applications in Neurosurgical Interventions
This comprehensive study explored the phytochemical properties of Nigella sativa L (N. sativa L) seeds essential oil using gas chromatography-mass spectrometry (GC-MS) analysis, with a specific focus on its potential compound Thymoquinone (TQ) exhibiting antimicrobial activity against Staphylococcus aureus (S. aureus) in the context of neurosurgical interventions.The study employs a meticulous methodology, encompassing the preparation of N. sativa essential oil, qualitative phytochemical screening, quantitative GC-MS analysis, and the antimicrobial analysis, employing Disc Diffusion, Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) evaluations to demonstrate the substantial inhibitory and bactericidal effects against Staphylococcus aureus (S.aureus